Report on professional attachment with Singapore Polymer Corporation (Private) Limited. - Ng, Chen Nee. (2009)
The purpose of this report is to provide an overview of my training experience at Singapore Polymer Corporation (Private) Limited (SPC Polymer), a manufacturer of plastic raw materials. This medium-sized company was founded in 1969 and it has two plants in Jurong. Its goal is to satisfy its "internal and external customers with consistent quality products and services through a total committed effort to quality improvements".